A1 and A2A Adenosine receptors expression in ALS transgenic mice for the human gene SOD1 - Ramos, Gonçalo Luis Monteiro, 1988- (2013)
Tese de mestrado. Biologia (Biologia Molecular e Genética). Universidade de Lisboa, Faculdade de Ciências, 2012